2005
DOI: 10.1615/jenvpathtoxoncol.v24.i3.60
|View full text |Cite
|
Sign up to set email alerts
|

Use of Black Tea in Modulating Clastogenic Effects of Arsenic in Mice In Vivo

Abstract: The concentration of arsenic in drinking water has far exceeded the permissible limit of 0.001 mg/L and has reached epidemic proportions, with a maximum of 3.7 mg/L in several districts of West Bengal and in the adjoining Bangladesh. Because inorganic arsenic is a documented human carcinogen, arsenic in drinking water may cause 200,000-270,000 deaths per year from cancer in India alone. Tea has a protective effect against the clastogenicity of arsenic. We investigated whether tea extracts could protect against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The phytochemicals induced various DNA repair enzymes, such as PARP1, DNA β-polymerase, XRCC1, DNA ligase III, DNA protein kinase (catalytic subunit), XRCC 4, DNA ligase IV, and DNA topoisomerase Iiβ. Thus, the authors suggested that tea polyphenols may effectively counter oxidative DNA damage and inhibition of DNA repair induced by sodium arsenite [ 90 92 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemicals induced various DNA repair enzymes, such as PARP1, DNA β-polymerase, XRCC1, DNA ligase III, DNA protein kinase (catalytic subunit), XRCC 4, DNA ligase IV, and DNA topoisomerase Iiβ. Thus, the authors suggested that tea polyphenols may effectively counter oxidative DNA damage and inhibition of DNA repair induced by sodium arsenite [ 90 92 ].…”
Section: Introductionmentioning
confidence: 99%
“…Those enzymes are involved in cellular detoxification, and genetic variants are created by this heavy metal. Since the State of West Bengal in India is reported to have high content of arsenic in its groundwater [4,5], we have included this region in our study in order to find out if there is any possible link between this metal toxicity in the oral carcinoma. This is a case control study carried out in our hospital in order to compare the arsenic (As) concentration in hair samples, frequency of micronuclei in buccal smear of patients -with those in the control population.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many countries like Taiwan (mainly Central and Eastern parts) have alarming levels of oral cancer incidence [6], many cases accounting to the arsenic exposure. Since West Bengal has been known to be an arsenic prone state [7], we have chosen this zone in our study to find out a possible correlation between the arsenic toxicity and the development of oral malignancy.…”
Section: Introductionmentioning
confidence: 99%